The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.tjem.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical characteristics among Turkish homeless patients presenting to the emergency department

Abstract: ObjectiveSince the homeless are at greater risk of encountering health problems than the general population, the reasons for and incidence of their presentations to emergency departments also vary. The purpose of this study was to determine the sociodemographic and clinical characteristics of Turkish homeless patients who brought to the emergency department by ambulance.Materials and methodsThe records of homeless adult patients brought to the ED by 112 emergency service ambulance teams over a 1-year period fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…This is not a solely economic issue, but also a problem of patient exposure to cumulative doses of ionizing radiation [ 30 ]. These results differ from those reported by Yeniocak et al [ 17 ], where homeless patients admitted for trauma as well as for non-trauma-related reasons, had radiological examinations performed as standard. The percentage of CT scans performed was 3 times less than all X-ray examinations performed.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is not a solely economic issue, but also a problem of patient exposure to cumulative doses of ionizing radiation [ 30 ]. These results differ from those reported by Yeniocak et al [ 17 ], where homeless patients admitted for trauma as well as for non-trauma-related reasons, had radiological examinations performed as standard. The percentage of CT scans performed was 3 times less than all X-ray examinations performed.…”
Section: Discussioncontrasting
confidence: 99%
“…No trend in the seasonal nature of admissions is also confirmed by Brown et al [ 16 ]. On the other hand, Yeniocak et al [ 17 ] pointed out a clear seasonal variation in the number of admissions of injured homeless patients. The vast majority of admissions of such patients occurred during the summer months, which is associated by the author with the increased presence of homeless people on the streets and thus a greater likelihood of exposure to injury.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory conditions contributed between 1.8% of ED attendance, in a study using national population data from the NHAMCS database, [ 40 ] to 15% in a study evaluating data of those brought by ambulance and non-trauma-related attendance [ 38 ]. Three studies reported both PEH and non-homeless data, producing RRs which ranged from 0.63 [ 40 ] to 1.01 [ 26 ].…”
Section: Resultsmentioning
confidence: 99%